Mutation of the Drosophila melanogaster L. under the influence of the electromagnetic radiation - Nykyforov, Volodymyr; Sakun, Oksana (Publishing House of Lviv Polytechnic National University, 2016)
Brief results of the previous studies of the effect of electromagnetic radiation on the fruit flies are quoted. The influence of electromagnetic radiation of industrial frequency on the living organisms has been investigated. Correlative dependence between phenotype Drosophila melanogaster L., duration and intensity of harmful factors has been established. Phenotypic manifestations have been fixed and Drosophila melanogaster L. mutation under the constant influence of the magnetic field induction from 2,25 to 20 μТ in three generations of test objects have been characterized. The dependence of the increased frequency of mutations occurrence and the increase of their diversity caused by the increase of magnetic field induction has been revealed.
Keywords: electromagnetic radiation; electromagnetic pollution; test objects; mutation